Excision of Colloid Cyst through Interhemispheric, Transcallosal, Transcavum, Interfornicial Approach - Kumar, Santosh; Sadashiva, Nishanth (Indian Journal of Neurosurgery, 2021)
Colloid cysts (CC) occur predominantly in the midline with majority involving roof of the third ventricle. In cases of cavum septum pellucidum (CSP), the surgeon can lose orientation when normal intraventricular structures are not encountered during surgery. We report a patient with CSP, who underwent right frontal parasagittal craniotomy, interhemispheric, transcallosal approach to reach the lesion. Lesion may not be seen in its usual location of foramen of Monroe, and entering the cavum may be confusing because no intraventricular landmarks will be seen. Excision of the cyst through the cavum usually requires interfornicial approach, and this structure must be separated gently to avoid injury.
Keywords: colloid cyst; cavum septum pellucidum; interfornicial approach